Sex evolution path involved in flowering plant family Cucurbitaceae: A review - Pattnaik, Animesh; Prusty, Pradip Kumar; Barik, Madhusmita; Mishra, Rukmini; Mohanty, Jatindra Nath (Plant Science Today, 2025)
The predominant sexual system in the plant kingdom is hermaphroditism, where both female and male reproductive organs coexist within a single flower. The major parameters that influence the sexual systems are genetic variation, pollinator availability and type, mating system, ecological factors, geographical isolation, selective pressures, evolutionary history, polyploidy, hybridization and sexual conflict. These factors all play significant roles. Plants may evolve self-fertilization or outcrossing mechanisms based on their specific environmental conditions, reproductive strategies and evolutionary history. The interplay of these factors shapes the diverse range of sexual systems observed in plant species worldwide. The Cucurbitaceae family exhibits a highly specialized sex chromosome differentiation scheme with three major sexual patterns (monoecy, dioecy and hermaphroditism). In the present review, we focus on the evolution of gender in flowering plants of the Cucurbitaceae family, exploring the various paths and drivers involved in the evolution of dioecy. We also shed light on the sex chromosomes and phytohormones that contribute to gender diversification. Several molecular and genomic approaches have been recently applied to uncover the genetic basis of gender differentiation in different flowering plant species.